Improving Model and Data Integration Using MOSAIC as Central Data Management Platform. Issue 7 (4th June 2014) - Kraus, Robert; Fillinger, Sandra; Tolksdorf, Gregor; Minh, Duc H.; Merchan‐Restrepo, Victor A.; Wozny, Günter; Nilles, Michael; Wozny, Günter
Abstract In this paper, the problem of the data and model management in the lifecycle of a process plant is addressed by presenting the database structure of the modeling and optimization platform MOSAIC. The first step of data integration is done by combining models and plant data into one central database. This has advantages for both plant design and plant optimization. Basic engineering workflows can then be improved. Several database configurations are presented to meet the different requirements with respect to security and open access.